A Se···O bonding catalysis approach to the synthesis of calix[4]pyrroles - Tong, Qingzhe; Zhao, Zhiguo; Wang, Yao (Beilstein Journal of Organic Chemistry, 2022)
Described herein is a chalcogen bonding catalysis approach to the synthesis of calix[4]pyrrole derivatives. The Se···O bonding interactions between selenide catalysts and ketones gave rise to the catalytic activity in the condensation reactions between pyrrole and ketones, leading to the generation of calix[4]pyrrole derivatives in moderate to high yields. This chalcogen bonding catalysis approach was efficient since only 5 mol % catalyst loading was used to promote the consecutive condensation processes while the reactions could be carried out at room temperature, thus highlighting the potential of this type of nonclassical interactions in catalyzing relative complex transformations.
Keywords: calix[4]pyrrole; chalcogen bonding; ketones; Se···O bonding interactions; supramolecular catalysis